From the Clinic to the Laboratory, and Back Again: Investigations on Cannabinoids and Endocannabinoid System Modulators for Treating Schizophrenia - Hoffman, Kurt Leroy (Frontiers in Psychiatry, 2021)
The present mini-review will focus on some key animal models of schizophrenia that have explored the effects of pharmacological manipulations of the endocannabinoid system – by administering cannabidiol (CBD), cannabinoid receptor modulators, and inhibitors of FAAH – on behavioral and cognitive outcome measures. First, results of clinical studies that have explored the endocannabinoid system as a therapeutic target for schizophrenia are summarized, and then preclinical work on animal models of schizophrenia based on NMDA receptor antagonism or neurodevelopmental manipulations are discussed. A brief overview is given of the theoretical framework on which these models are based, along with a concise summary of results that have been obtained. Clinical results using CBD for schizophrenia seem promising but inconclusive, while its effects in animal models of schizophrenia largely support its potential as a useful pharmacotherapy. Animal models have been paramount for elucidating the function of the endocannabinoid system and for identifying novel pharmacological targets, such as cannabinoid receptors and anandamide. The objective of this review is, on the one hand, to emphasize the potential of such models to predict clinical response to experimental drugs, and on the other hand, to highlight areas in which research on such models could be improved.